Progressive Heritage : the Evolution of a Politically Radical Literary Tradition in Canada. - Doyle, James (Wilfrid Laurier University Press, 2006)
Most critics and literary historians have ignored Marxist-inspired creative literature in Canada, or dismissed it as an ephemeral phenomenon of the 1930s. Research reveals, however, that from the 1920s onward Canadian creative writers influenced by Marxist ideas have produced a quantitatively substantial and artistically significant body of poetry, drama, fiction, and non-fiction. This book traces historically and evaluates critically this tradition, with particular emphasis on writers who were associated with, or sympathetic to, the Communist Party of Canada. After two chapters surveying t.